An Analysis of Language Styles Used in the Daily Newspaper of Radar Selatan - Nurahma Wahyuni; Vebbi Andra; Heny Friantary (Jadila: Journal of Development and Innovation in Language and Literature Education, 2022)
Language styles are commonly used in newspapers intended to interact the readers’ reading interest and comprehension towards the delivered information. The aim of this research was to describe the language styles including the meaning used in the daily newspapers of Radar Selatan March 2021 edition. This research was designed by using a qualitative approach with a descriptive method. The research data was the news found in the daily newspapers of Radar Selatan March 2021 edition. The data was collected through observation and interview, and analyzed by using an analysis model proposed by Miles and Huberman. In this case, the researchers implemented triangulation techniques as the data validity technique of this research. The result of this research revealed that there were some types of language styles used in the daily newspapers of Radar Selatan March 2021 edition. The most dominant language styles found in the newspaper included: (1) metonymy, such as the use of some familiar and popular words used by the society, (2) parable, such as the use of parable to illustrate something based on the characteristics, (3) pars pro toto, (4) figurative language of association , (5) antanaclasis, (6) synecdoche, (7) epizeuxis, (8) eponymy, and (9) anaphora.